PENERAPAN MEDIA VIDEO EDUKATIF BERBASIS CAPCUT DALAM MENINGKATKAN KREATIVITAS BELAJAR SISWA DI MTS AL JAMA'IYAH - Hasibuan, M. Ridho Julpandra; Irawan, Putri; Surbakti, Taufiqurrahman; Siagian, Meryance Viorentina (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to develop and implement CapCut-based educational video media to enhance students’ learning creativity at MTs Al Jama’iyah. The research employed a Research and Development (R&D) method using the Borg & Gall development model. The research stages included needs analysis, media design, product development, validation by media experts and subject matter experts, and student trials. Data collection techniques consisted of observation, questionnaires, and documentation. The collected data were analyzed descriptively to determine the feasibility of the media and students’ responses to its implementation. The results showed that the CapCut-based educational video media was categorized as very feasible for use in learning based on the validation results from media experts and material experts. The implementation of the CapCut-based educational video media in the learning process was able to improve students’ learning creativity, as indicated by increased student participation, the ability to express ideas, and active involvement during learning activities. In addition, students’ responses to the use of CapCut-based educational video media were positive, with students feeling more interested, motivated, and assisted in understanding the learning materials. Based on these findings, it can be concluded that CapCut-based educational video media is effective as a learning medium and has the potential to enhance students’ learning creativity at MTs Al Jama’iyah. This media can serve as an innovative learning alternative that is relevant to technological developments and the demands of learning in the digital era. Keyword: Educational Video Media; CapCut, Learning Creativity; Research and Development; Borg & Gall Abstrak: Penelitian ini bertujuan untuk mengembangkan dan menerapkan media video edukatif berbasis CapCut dalam meningkatkan kreativitas belajar siswa di MTs Al Jama’iyah. Penelitian ini menggunakan metode Research and Development (R&D) dengan model pengembangan Borg & Gall. Tahapan penelitian meliputi analisis kebutuhan, perancangan media, pengembangan produk, validasi ahli media dan ahli materi, serta uji coba kepada siswa. Teknik pengumpulan data dilakukan melalui observasi, angket, dan dokumentasi. Data yang diperoleh dianalisis secara deskriptif untuk mengetahui kelayakan media dan respons siswa terhadap penggunaannya. Hasil penelitian menunjukkan bahwa media video edukatif berbasis CapCut dinyatakan sangat layak digunakan sebagai media pembelajaran berdasarkan hasil validasi ahli media dan ahli materi. Penerapan media video edukatif berbasis CapCut dalam proses pembelajaran mampu meningkatkan kreativitas belajar siswa, yang ditunjukkan melalui meningkatnya keaktifan siswa, kemampuan mengemukakan ide, serta keterlibatan siswa dalam kegiatan pembelajaran. Selain itu, respons siswa terhadap penggunaan media video edukatif berbasis CapCut menunjukkan hasil yang positif, di mana siswa merasa lebih tertarik, termotivasi, dan terbantu dalam memahami materi pembelajaran. Berdasarkan hasil penelitian tersebut, dapat disimpulkan bahwa media video edukatif berbasis CapCut efektif digunakan sebagai media pembelajaran dan berpotensi meningkatkan kreativitas belajar siswa di MTs Al Jama’iyah. Media ini dapat dijadikan sebagai alternatif pembelajaran yang inovatif dan relevan dengan perkembangan teknologi serta kebutuhan pembelajaran di era digital. Kata kunci: Media Video Edukatif; Capcut, Kreativitas Belajar; Research and Development; Borg & Gall